Making an Effort Versus Experiencing Load - Melina Klepsch; Tina Seufert (Frontiers in Education, 2021)
In cognitive load theory (CLT), the role of different types of cognitive load is still under debate. Intrinsic cognitive load (ICL) and germane cognitive load (GCL) are assumed to be highly interlinked but provide different perspectives. While ICL mirrors the externally given task affordances which learners experience passively, germane resources are invested by the learner actively. Extraneous affordances (ECL) are also experienced passively. The distinction of passively experienced load and actively invested resources was inspired by an investigation where we found differential effects of a learning strategy training, which in fact resulted in reduced passive load and increased actively invested effort. This distinction is also mirrored in the active and passive forms for effort in German language: “es war anstrengend” (it has been strenuous) vs. “ich habe mich angestrengt” (I exerted myself). In two studies, we analyzed whether we could distinguish between these active and passive aspects of load by using these phrases and how this distinction relates to the three-partite concept of CLT. In two instructional design studies, we included the active and passive items into a differentiated cognitive load questionnaire. We found the factor structure to be stable, with the passive item loading on the ICL factor and the active item loading on the GCL factor. We conclude that it is possible to distinguish between active and passive aspects of load and that further research on this topic could be constructive, especially for learning tasks where learners act in a more self-regulated way and learner characteristics are taken into account.